Correlation between pulpal and carotid arteries blood flow in two age groups - Dželetović Bojan; Aleksić Nikola; Grga Đurica; Savić-Stanković Tatjana; Milanović Ivana; Radak Đorđe (Serbian Medical Society - Dental Section, Belgrade, 2015)
Introduction Vascular network of dental pulp is supplied through common and external carotid artery and terminal dental branches that supply each pulp tissue. Age related changes of pulp tissue influence pulpal vascularization as well. The aim of this study was to compare and correlate pulpal and common and external carotid artery blood flow in young and middle age individuals of general population. Material and Methods Two groups of 10 participants were included in the study, young (20-25 years) and middle age (50-55 years) group. Pulpal blood flow (PBF) measurements on intact right and left upper central incisors were performed using laser Doppler flowmetry (LDF) method. Carotid arteries blood flow was assessed using carotid ultrasonography. Results PBF levels were significantly higher in young (3.11±0.67 and 3.46±1.11, right and left upper central incisors, respectively) compared to middle age (1.93±0.47 and 2.30±0.64, right and left upper central incisors, respectively) participants (independent sample t test; p<0.05). There was no correlation between common and external carotid artery blood flow and upper central incisors PBF in young as well as middle age participants, for right or left side. Conclusion Absence of correlation between carotid arteries blood flow and PBF suggests that reduced PBF in middle age participants was probably not due to reduced blood supply from carotid arteries but it was result of age related changes at the level of pulpal blood vessels.